Anthropometric characteristics of young Italian tennis players - Elce, A.; Cardillo, G.; Ventriglia, M.; Giordano, C.; Amirante, F.; Mazza, G.; Sangiorgio, A.; Martiniello, L. (Journal of Human Sport & Exercise, 2017)
Purpose. Aim of our study is to observe specific body differences induced by training in young agonist tennis players at pre-pubertal and pubertal age, using anthropometry. Method. We analyzed 101 tennis players (27 females and 74 males) coming from South Italy, aged 8-14, which played tennis from at least 1 year. Anthropometric measurements like wrist, mid-thigh, mid-arm circumferences and arms length were compared between dominant and not dominant side of the body. Results. The mean Z-score for females was 0.9627, corresponding to the 83.22th centile of Italian growth chart, the mean Z-score for males was 1.0157, corresponding to 84.51th centile of Italian growth chart. For weight the mean Z-score for females was 0.2394 (59.46th centile) and the mean Z-score for males was 0.4032 (65.66th centile). The mean Z-score for females Body Mass Index was -0.1451 (44.23th centile), instead the mean Z-score for males was -0.0768 (46.94th centile). The Wilcoxon test reported a statistically significant difference between dominant and not dominant wrist circumferences regardless of sex (p-value=1.87e-10). Conclusions. Our study revealed that playing tennis starting from childhood may be useful for a regular growth. Analysis of wrist circumference and height may confirm the osteogenic potential of the sport.